THE INFLUENCE OF KEY OPINION LEADERS (KOL) AND CUSTOMER RELATIONSHIP MANAGEMENT (CRM) ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS A MEDIATING VARIABLE IN IBOX - Chandra, Zelindio; Christian, Michael (Ridwan Institute, 2024)
This study aims to examine the influence of Key Opinion Leaders (KOLs) and Customer Relationship Management (CRM) on IBOX customer loyalty and satisfaction, as well as the role of customer satisfaction as a mediator in the relationship between KOLs and CRM with loyalty. This study uses a quantitative approach with an explanatory research design to test the cause-and-effect relationship between key opinion leaders, CRMs, and customer loyalty as independent variables, the mediating role of Customer Satisfaction (KP), and the mediator role of the customer satisfaction (LP). The study population consists of Greater Jakarta residents aged 19-55 years who are active in using the internet, with a sample selected by purposive sampling of 250 respondents. The results show that customer satisfaction has a significant influence on customer loyalty (P0.05), with each variable showing a p-value smaller than 0.05, namely 0.000 and 0.011, respectively. In addition, this study also revealed that Customer Service Management (CRM) has an important influence on Customer Loyalty (LP), with the p value of 0.000. This shows that KOL and CRM not only affect customer satisfaction, but also play an important role in building customer loyalty.